Transgene Silencing Following Lentiviral Gene Delivery into Hematopoietic Stem Cells - Ngai, Siew Ching (2011)
Gene therapy shows increasing promise for the treatment of hematopoietic inherited diseases such as β-thalassemia. One of the main barriers for a successful gene therapy is the short-lived duration of gene expression in vivo, a phenomenon known as transgene silencing. Unlike other viral methods, lentiviral vectors (LVs) are attractive gene transfer vehicles due to their ability to transduce non-dividing cells such as hematopoietic stem cells (HSCs) efficiently. The objectives of this study are to evaluate if the HSCs transduced by LV are subject to transgene silencing, and to determine the factors that contribute to this event. The LV carrying green fluorescent protein (GFP) driven by ubiquitin C (UbC) promoter (LV/UbC/GFP) and LV carrying GFP driven by cytomegalovirus (CMV) promoter with additional cis-acting elements (LV/CMV/GFP) were produced. The purpose for having these two LVs was to observe if the LV with UbC promoter could drive a respectable level and prolonged duration of reporter gene expression in comparison to LV/CMV/GFP in vitro. Unfortunately, although UbC promoter has been shown to exhibit robust and prolonged gene expression in a non-viral context, LV/UbC/GFP failed to measure up to the level and duration of gene expression displayed by LV/CMV/GFP with the two cis-acting elements, which the values were up to more then 90% of GFP expression. Next, HSCs (Lin-cKit+) isolated from the femurs and tibias of BALB/c mice were transduced with LV/CMV/GFP. The result showed that the GFP expression declined over time, from 17.08% (Highest expression) at day 2 post-transduction to 4.27% (Lowest expression) at day 7 post-transduction, which was the duration of this experiment. DNA methylation and histone modification were investigated whether they were factors involved in the short duration of GFP expression, by treating the cells with 5-azacytidine (5-azaC) (DNA demethylating agent), trichostatin A (TSA) (histone deacetylase inhibitor) or the combination of both drugs to prevent and to reverse the silencing effect. As the 5-azaC and the TSA could modulate the GFP gene expression up to 70%, this implies that the DNA methylation and histone modification were associated with the silencing event. To confirm this, sodium bisulfite sequencing and chromatin immunoprecipitation (ChIP) assay were performed on HSCs harvested on the day of initial gene expression and on the day of gene silencing. DNA methylation occurred soon after LV transduction. In addition, on the day of gene expression (Day 2 post-transduction), the CMV promoter was acetylated and in a euchromatin state while the GFP reporter gene was acetylated but in a heterochromatic state. On the day of gene silencing (Day 7 post-transduction), the CMV promoter was in a heterochromatic state whereas the GFP reporter gene was deacetylated and in a heterochromatic state. Finally, allogeneic HSC transplantation was performed in irradiated BALB/c mice. The transplanted HSCs robustly reconstituted all blood cell lineages. However, the GFP expression in different cell types of different organs declined over time, reaching the baseline level at day 7 post-transplantation. It is believed that similar in vitro silencing mechanisms were involved in this phenomenon in vivo. In conclusion, this study has shown that (1) Transgene silencing occurs in LV-transduced HSCs in vitro and following transplantation in mice, and (2) DNA methylation and histone modification are involved in transgene silencing in vitro. Strategies to overcome this problem need to be developed before the ultimate goal for a permanent therapeutic response in gene therapy for β-thalassemia can be achieved.